The operational implications of donor behaviors following enrollment in STRIDE (Strategies to Reduce Iron Deficiency in blood donors). Issue 10 (13th July 2017) - Cable, Ritchard G.; Birch, Rebecca J.; Spencer, Bryan R.; Wright, David J.; Bialkowski, Walter; Kiss, Joseph E.; Rios, Jorge; Bryant, Barbara J.; Mast, Alan E.
Abstract : BACKGROUND: Donor behaviors in STRIDE (Strategies to Reduce Iron Deficiency), a trial to reduce iron deficiency, were examined. STUDY DESIGN AND METHODS: Six hundred ninety‐two frequent donors were randomized to receive either 19 or 38 mg iron for 60 days or an educational letter based on their predonation ferritin. Compliance with assigned pills, response to written recommendations, change in donation frequency, and future willingness to take iron supplements were examined. RESULTS: Donors who were randomized to receive iron pills had increased red blood cell donations and decreased hemoglobin deferrals compared with controls or with pre‐STRIDE donations. Donors who were randomized to receive educational letters had fewer hemoglobin deferrals compared with controls. Of those who received a letter advising of low ferritin levels with recommendations to take iron supplements or delay future donations, 57% reported that they initiated iron supplementation, which was five times as many as those who received letters lacking a specific recommendation. The proportion reporting delayed donation was not statistically different (32% vs. 20%). Of donors who were assigned pills, 58% reported taking them "frequently, " and forgetting was the primary reason for non‐compliance. Approximately 80% of participants indicated that they would take iron supplements if provided by the center. CONCLUSIONS: Donors who were assigned iron pills had acceptable compliance, producing increased red blood cell donations and decreased low hemoglobin deferrals compared with controls or with pre‐STRIDE rates. The majority of donors assigned to an educational letter took action after receiving a low ferritin result, with more donors choosing to take iron than delay donation. Providing donors with information on iron status with personalized recommendations was an effective alternative to directly providing iron supplements.